Total escape of SARS-CoV-2 from dual monoclonal antibody therapy in an immunocompromised patient - Lena Jaki; Sebastian Weigang; Lisa Kern; Stefanie Kramme; Antoni G. Wrobel; Andrea B. Grawitz; Philipp Nawrath; Stephen R. Martin; Theo Dähne; Julius Beer; Miriam Disch; Philipp Kolb; et al. (Nature Communications, 2023)
Abstract Monoclonal antibodies (mAbs) directed against the spike of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are effective therapeutic options to combat infections in high-risk patients. Here, we report the adaptation of SARS-CoV-2 to the mAb cocktail REGN-COV in a kidney transplant patient with hypogammaglobulinemia. Following mAb treatment, the patient did not clear the infection. During viral persistence, SARS-CoV-2 acquired three novel spike mutations. Neutralization and mouse protection analyses demonstrate a complete viral escape from REGN-COV at the expense of ACE-2 binding. Final clearance of the virus occurred upon reduction of the immunosuppressive regimen and total IgG substitution. Serology suggests that the development of highly neutralizing IgM rather than IgG substitution aids clearance. Our findings emphasise that selection pressure by mAbs on SARS-CoV-2 can lead to development of escape variants in immunocompromised patients. Thus, modification of immunosuppressive therapy, if possible, might be preferable to control and clearance of the viral infection.